# How do you solve #a^2+11a=-18#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation ( a^2 + 11a = -18 ), you can follow these steps:

- Rewrite the equation in standard quadratic form: ( a^2 + 11a + 18 = 0 ).
- Factor the quadratic expression: ( (a + 2)(a + 9) = 0 ).
- Set each factor equal to zero and solve for ( a ):
- ( a + 2 = 0 ) yields ( a = -2 ).
- ( a + 9 = 0 ) yields ( a = -9 ).

So, the solutions to the equation ( a^2 + 11a = -18 ) are ( a = -2 ) and ( a = -9 ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7